Systemic Inflammation in Chronic Obstructive Pulmonary Disease: May Adipose Tissue Play a Role? Review of the Literature and Future Perspectives - Ruzena Tkacova (Mediators of Inflammation)
Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. Low-grade systemic inflammation is considered a hallmark of COPD that potentially links COPD to increased rate of systemic manifestations of the disease. Obesity with/without the metabolic syndrome and cachexia represent two poles of metabolic abnormalities that may relate to systemic inflammation. On one hand systemic inflammatory syndrome likely reflects inflammation in the lungs, i.e. results from lung-to plasma spillover of inflammatory mediators. On the other hand, obesity-related hypoxia results in local inflammatory response within adipose tissue per se, and may contribute to elevations in circulatory mediators by spillover from the adipose tissue to the systemic compartment. The extent to which systemic hypoxia contributes to the adipose tissue inflammation remains unknown. We assume that in patients with COPD and concurrent obesity at least three factors play a role in the systemic inflammatory syndrome: the severity of pulmonary impairment, the degree of obesity-related adipose tissue hypoxia, and the severity of systemic hypoxia due to reduced pulmonary functions. The present review summarizes the epidemiological and clinical evidence linking COPD to obesity, the role of adipose tissue as an endocrine organ, and the role of hypoxia in adipose tissue inflammation.